Ubiquitous positioning [ - Mannings, Robin (Artech House GNSS library, 2008)
Introduces practitioners to the field of Ubiquitous Positioning - positioning systems that identify the location and position of people, vehicles and objects in time and space in the digitised networked economy. This volume explores ubiquitous computing from a convergence perspective, offering a road map to this field